Surface Stabilization of O3-type Layered Oxide Cathode to Protect the Anode of Sodium Ion Batteries for Superior Lifespan - Qi Zhang; Qin-Fen Gu; Yang Li; Hai-Ning Fan; Wen-Bin Luo; Hua- Kun Liu; Shi-Xue Dou (iScience, 2019)
Summary: Even though the energy density of O3-type layer-structured metal oxide cathode can fully reach the requirement for large-scale energy storage systems, the cycling lifespan still cannot meet the demand for practical application once it is coupled with a non-sodium-metal anode in full-cell system. Transition metal dissolution into the electrolyte occurs along with continuous phase transformation and accelerates deterioration of the crystal structure, followed by migration and finally deposition on the anode to form a vicious circle. Surface engineering techniques are employed to modify the interface between active materials and the electrolyte by coating them with a thin layer of AlPO4 ion conductor. This stable thin layer can stabilize the surface crystal structure of the cathode material by avoiding element dissolution. Meanwhile, it can protect the anode from increased resistance by suppressing the dissolution-migration-deposition process. This technique is a promising method to improve the lifetime for the future commercialization. : Energy Storage; Surface Treatment; Materials Characterization Subject Areas: Energy Storage, Surface Treatment, Materials Characterization